Updating freeTribe to Support Efficient Synchronous Awareness in the Web Context - Ricardo Delgadillo; Eduardo Escofet; Humberto Rodríguez-Avila; Julio C. Rodríguez-Cano (ReCIBE, 2013)
The research field of Computer-Supported Cooperative Work has been reflected fundamentally in theoretical contributions. This contributions have constitute the base to carry out several intents to facilitate the work of the collaborative systems developers, however, current tool-kits, APIs or class libraries only eliminate partially the gap between the technical aspects that impose the information technology and the stressed social character of the process of collaboration in the World Wide Web. In this paper is presented the framework freeTribe, which involve the domain of the distributed groupwares leaning on the Cooperative Model of the methodology AMENITIES, in the middleware platform ICE and in RIA technologies; freeTribe has been designed as a software framework, to maximize its reusability and adaptability with a minimal programming effort. Support for synchronous group tasks in the Web context is increasingly recognized as a desideratum for collaborative systems and several tools have emerged recently that help groups of people with the same goals to work together, but many issues for these collaborative systems remain under studied. We identified synchronous awareness as one of these issues in collaborative systems, and updated freeTribe with four well-accepted kinds of awareness (group awareness, workspace awareness, contextual awareness, and peripheral awareness) by the community focusing our interest in its synchronous mechanism for efficient interaction in Web contexts.